PEMANFAATAN X PADA AKUN AUTOBASE @JDRAMAFESS SEBAGAI MEDIA KOMUNIKASI DI KALANGAN PENGGEMAR DRAMA JEPANG - Adhary, Adinda Fara (Jurnal Common, 2024)
Technological developments have resulted in the proliferation of Japanese pop culture worldwide, Indonesia is one of the countries that feels the impact of Japanese pop culture. One form of Japanese pop culture that is currently in demand among Japanese pop fans in Indonesia is Japanese drama. This phenomenon led to the creation of the autobase account @jdramaafess on the X social media application, which aims to be a communication medium for seeking information and discussing Japanese dramas as well as a means of increasing relationships between fans. This research uses a descriptive qualitative approach through in-depth interviews, observation and documentation. The sampling technique was carried out using snowball sampling, where the informant selection process was based on the consideration that the data source with information was relevant and appropriate to the research problem. The subjects in this research were autobase followers @jdramaafess who are fans of Japanese dramas. The informants selected in this study were 5 people. The results of this research show that Japanese drama fans can make very good use of the @jdramaafess autobase account as a communication medium, including in obtaining information needs, a place to build relationships, a means of education, and a means of entertainment. Keywords: Japanese Pop Culture, Japanese Drama, Autobase, X (Twitter).